PERAN ACCOUNT EXECUTIVE DI ERA DIGITAL DALAM PROSES PERENCANAAN IKLAN - Ardiman Tampubolon; Glorya Agustiningsih (Jurnal Komunikasi dan Bisnis, 2019)
The development of the advertising industry has experienced many changes over time, but as the development of the advertising industry is not followed by the development of the ability of skilled human resources in it, especially in the duties and roles of an Account Executive in an advertising company. The task of account executive in the digital era is not the same as the previous era, therefore it is necessary to have special skills and have more knowledge about the advertising industry today. The purpose of this study is to determine the development of the role of account executives in advertising companies today, which are caused by changes in the industrial era and the development of the advertising revolution in today's digital era.Keywords: Account Management, Account Executive, Advertising.